PREDICTED SEDIMENTARY SECTION OF SUBGLACIAL LAKE VOSTOK - G. Leychenkov I.; A. Popkov M.; Г. Лейченков Л.; А. Попков М. (Ice and Snow, 2015)
In early February 2012, the drill hole at the Vostok Station encountered theLakeVostokwater. This step is important to study the lake composition including possible microbial life and to model subglacial environments however, the next ambitious target of the Vostok Drilling Project is sampling of bottom sediments, which contain the unique record of ice sheet evolution and environmental changes in centralAntarcticafor millions of years. In this connection, the forecast of sedimentary succession based on existing geophysical data, study of mineral inclusions in the accretion ice cores and tectonic models is important task. Interpretation of Airborne geophysical data suggests thatLakeVostokis the part of spacious rift system, which exists at least from Cretaceous. Reflection and refraction seismic experiments conducted in the southern part ofLakeVostokshow very thin (200–300 m) stratified sedimentary cover overlying crystalline basement with velocity of 6.0–6.2 km/s. At present, deposition in southernLakeVostokis absent and similar conditions occurred likely at least last3 m.y. when ice sheet aboveLakeVostokchanged insignificantly. It can be also inferred that from the Late Miocene the rate of deposition inLakeVostokwas extremely low and so the most of sedimentary section is older being possibly of Oligocene to early to middle Miocene age when ice sheet oscillated and deposition was more vigorous. If so, the sampling of upper few meters of this condensed section is very informative in terms of history of Antarctic glaciation. Small thickness of sedimentary cover raises a question about existence of lake (rift) depression during preglacial and early glacial times. После достижения скважиной 5Г на станции Восток поверхности оз. Восток перед исследователями стоит следующая важнейшая задача – проникновение в донные осадки, которые несут важнейшую информацию о подледной экосистеме и изменениях природной среды Антарктиды в геологическом прошлом. Депрессия подледникового оз. Восток представляет собой рифтовый грабен на ...